Frequency of Aspirin Misuse Among Hypertensive Patients in Babylon Province (Medico Legal Update, 2020)
Background: Hypertension endangering a risk of cardiovascular events and BP reduction will reduce suchcomplications. the role of aspirin in hypertension is debated, however it is advised in primary prevention incase of patient with high risk factors assessed by one of the cardiovascular risk calculator, a state in whichthe benefit of aspirin outweigh the risk of complications.Objectives: Estimate the prevalence of aspirin misuse in hypertensive patients ,which population at risk andestimate the possible source of this misuse habit.Patients and Methods: A cross sectional study that has been conducted in babil city major hospitals forthe period from the 20th of January to 2nnd of May. our study sample included 353 patients all cases werebetween 35 to 75 years old who attend to internal medicine outpatient clinic , emergency departments andinpatients of the above hospitals . All patient had hypertension being treated with antihypertensive agentsand they did not experience any vascular events like CVA, IHD and PVD. Results: 30.59% of patient do not use aspirin and 64.31 % of patients use aspirin prescribed by doctors.Most of aspirin use was according to doctor advice( 92.7%). 5.1 a use aspirin by advice from others. Aspirinuse was more with increased age group (p value 0.003) and in females( p value is 0.04). No significantdifferences between educational level, economic status, residency and occupation with the use of aspirin.Regarding aspirin intake by their doctors and score